Comparison of major medicinal components in the fibrous root of Epimedium brevicornu Maxim (Bangladesh Journal of Botany, 2019)
The contents of main medical components in the fibrous root and medicinal materials of Epimedium brevicornu Maxim was compared. The contents of epimedin C and icariin in the fibrous root and other parts of E. brevicornu were determined with RP-HPLC. The results showed that there were high contents of medical components in the fibrous root of E. brevicornu. The content of epimedin C in E. brevicornu fibrous root was obviously higher than that of other parts. The content of icariin in E. brevicornu fibrous root was close to that in the rhizome and apparently higher than that in the stem and petiole. The contents of epimedin C and icariin in the stem (including petiole) were lowest in all parts of E. brevicornu. The fibrous root cut from rhizome when cultivate E. brevicornu should be collected and utilized as medicinal materials.